Kerjasama Orangtua dan Guru Pendidikan Agama Islam dalam Meningkatkan Mutu Pendidikan Agama Islam - Nobisa, Yahya Nikmad (Prodi Pendidikan Agama Islam, 2022)
The aims of this study are: 1) to determine the duties and obligations of teachers/parents in student learning activities. 2) to find out the forms of cooperation between teachers and parents in improving the quality of Islamic religious education. The results of this study illustrate that the duties and obligations of teachers/parents in student learning activities are very important without the support of parents and teachers, so the knowledge of Islamic religious education in students cannot be achieved. While the forms of cooperation between parents and teachers in improving the quality of Islamic religious education are providing moral development, aqidah, character, being honest, fair and coaching away from envy.